Triiodothyronine and breast cancer - De Sibio, Maria Teresa (Baishideng Publishing Group Inc, 2014)
The thyroid hormones (THs), triiodothyronine (T3) and thyroxine (T4), are essential for survival; they are involved in the processes of development, growth, and metabolism. In addition to hyperthyroidism or hypothyroidism, THs are involved in other diseases. The role of THs in the development and differentiation of mammary epithelium is well established; however, their specific role in the pathogenesis of breast cancer (BC) is controversial. Steroid hormones affect many human cancers and the abnormal responsiveness of the mammary epithelial cells to estradiol (E2) in particular is known to be an important cause for the development and progression of BC. The proliferative effect of T3 has been demonstrated in various types of cancer. In BC cell lines, T3 may foster the conditions for tumor proliferation and increase the effect of cell proliferation by E2; thus, T3 may play a role in the development and progression of BC. Studies show that T3 has effects similar to E2 in BC cell lines. Despite controversy regarding the relationship between thyroid disturbances and the incidence of BC, studies show that thyroid status may influence the development of tumor, proliferation and metastasis.